Thirteen-year viral suppression and immunologic recovery of LPV/r-based regimens in pediatric HIV treatment: a multicenter cohort study in resource-constrained settings of China - Lao, Xiaojie; Zhang, Hanxi; Yan, Liting; Zhao, Hongxin; Zhao, Qingxia; Lu, Hongyan; Chen, Yuewu; Li, Huiqin; Chen, Jinfeng; Ye, Fuxiu; Yu, Fengting; Xiao, Qing; et al. (Frontiers in Medicine, 2023)
Background: Antiretroviral Therapy (ART) in children remains challenging due to resource-constrained settings. We conducted a thirteen-year, prospective, multicenter cohort study on the effectiveness and safety of LPV/r-based regimens in ART-naive and ART-experienced children. Methods From January 2008 to May 2021, children living with HIV-1 were recruited with LPV/r-based regimens from 8 clinical research sites in 6 provinces in China. Effectiveness outcomes were virologic failure (defined as at least two consecutive measurements of VL > 200 copies/mL after six months of ART) and immune response (defined as CD4% recovered to more than 25% after 12 months of treatment). The safety outcomes were treatment-related grade 2-4 adverse events and abnormal laboratory test results. Results A total of 345 ART-naïve children and 113 ART-experienced children were included in this cohort study. The median follow-up time was 7.3 (IQR 5.5–10.5) years. The incidence density of virologic failure was 4.1 (95% CI 3.3–4.9) per 100 person-years in ART-naïve children and 5.0 (95% CI 3.5–6.5) per 100 person-years in ART-experienced children. Kaplan Meyer (KM) curve analysis showed children with ART experience were at a higher risk of virologic failure (P < 0.05). The risk factors of virologic failure in ART-naïve children were clinic setting in rural hospitals (aHR = 2.251, 1.108–4.575), annual missed dose times > 5 days of LPV intake (aHR = 1.889, 1.004–3.554); The risk factor of virologic failure in ART-experienced children was missed dose times > 5 days (aHR = 2.689, 1.299–5.604) and mother as caregivers for ART administration (aHR = 0.475, 0.238–0.948). However, during long-term treatment, viral suppression rates between ART-naïve and ART-experienced children remained similar. No significant differences were observed in the immune response, treatment-related grade 2–4 events, and abnormal laboratory test results between ART-naïve children and ART-experienced children. Conclusions Our research underscores that with consistent, long-term treatment of LPV/r-based regimens, ART-experienced children can achieve therapeutic outcomes comparable to ART-naïve children. It provides crucial insights on LPV/r-based regimens in pediatric HIV treatment, especially in resource-limited settings where high-cost Integrase Strand Transfer Inhibitors (INSTs) are inaccessible. This evidence-based understanding provides an essential addition to the global therapeutic strategies for pediatric HIV treatment.